Pemberdayaan Masyarakat Terhadap Petani Jagung dalam Mengolah Kulit Jagung Menjadi Kerajinan Tangan - Festy Azkia Fais; Solfema Solfema; Lili Dasa Putri (Universitas Palangka Raya, 2025)
Community empowerment is a development program to build and increase community participation. Empowerment is useful for training the skills of individuals and groups of the surrounding community so that it can improve the community's economy. The implementation of empowerment will be more effective and efficient if there is a role for the government, community, and other supporting parties in the empowerment activities. Corn is one of the plants that has a thousand benefits such as corn kernels can be used for animal feed, consumed as a staple food to replace rice, the skin can be used to make handicrafts such as photo frames, key chains, and others.